Antibiofilm and Antimicrobial Activities of Chloroindoles Against Uropathogenic Escherichia coli - Boya, Bharath Reddy; Lee, Jin-Hyung; Lee, Jintae (Frontiers in Microbiology, 2022)
Uropathogenic E. coli (UPEC) is a nosocomial pathogen associated with urinary tract infections and expresses several virulence factors that cause recurring infections and cystitis of the bladder, which can lead to pyelonephritis. UPEC uses different types of extracellular appendages like fimbriae and pili that aid colonization and adherence to bladder epithelium and can form biofilm-like bacterial communities that aid its survival after the deployment of host immune responses. We investigated the antibiofilm, antimicrobial, and antivirulence properties of three indole derivatives, namely, 4-chloroindole, 5-chloroindole, and 5-chloro 2-methyl indole. These three chloroindoles had MIC’s of 75 μg/ml and inhibited biofilm formation by an average of 67% at 20 μg/ml. In addition, they inhibited swarming and swimming motilities, which are essential for dissemination from bacterial communities and colonization, reduced cell surface hydrophobicity, and inhibited indole production and curli formation. Gene expression analysis showed all three chloroindoles significantly downregulated the expressions of virulence genes associated with adhesion, stress regulation, and toxin production. A 3D-QSAR analysis revealed substitutions at the 4th and 5th positions of the indole moiety favored antimicrobial activity. Furthermore, these chloroindoles potently inhibited biofilm formation in other nosocomial pathogens and polymicrobial consortia.